ESTUDO CINÉTICO DA ELETRO-OXIDAÇÃO DE ÁCIDO FÓRMICO SOBRE ELETRODO DE PLATINA POLICRISTALINA - Emiliano, Carla Bandeira (2014)
The search for fuel cells economically viable have been subject of study for many researchers, in order to use organic molecules of low molecular weight as fuel for these systems. Electrochemical cells containing organic molecules, such as methanol, ethanol and formic acid have also some highlight in dynamic system studies, which are out of thermodynamic equilibrium. Therefore, the present study makes a review about electrochemical techniques used for formic acid oxidation system characterization, in order to understand kinetic and mathematical aspects described on other papers in this area. It were performed voltammetric experiments, in which one realizes that scan rate, the use of rotatory electrode and formic acid concentration are important factors in reaction rate. One can, thus, including steps or variables associated with diffusion in the proposed models. Experiments with changes on the inversion potential show that the platinum oxides have influence on voltammetric peaks characteristics. Potential oscillations show the features presented by several other authors; however, mathematical models don`t cover all aspects experimentally observed neither for potential oscillations nor to voltammetric conditions. One realizes that induction time increases with increasing the rotating speed, what is not described in the literature. IES experiments show common features described in others papers in the area. Nevertheless, one realizes the obvious requirement for modification of mathematical models found in the literature, in order to cover all the particularities observed in the experiments